Pharmacological profile of prescriptions containing antidepressants - Prafull Mohan; Harpreet Singh; Sharmila Sinha; K Prabhakaran (Journal of Marine Medical Society, 2021)
Background: The prescription of antidepressants is increasing due to the increasing incidence of depression and the use of antidepressants in other indications. There is a need to monitor their prescription practices not only to ensure evidence-based clinical use but also to align classroom teaching with the current clinical trends. Materials and Methods: This observational study was conducted in the department of psychiatry of a tertiary care hospital in western Maharashtra on anonymized prescriptions received within the study period. Results: A total of 214 prescriptions were analyzed with 268 instances of antidepressant prescription. 59.05% of prescriptions were of selective serotonin reuptake inhibitors (SSRIs), 18.11% of atypical antidepressants, 16.92% of tricyclic antidepressants (TCAs), and 5.90% of serotonin-noradrenaline reuptake inhibitors. 46% percent of prescriptions were as per defined daily doses (DDDs), 26% more than DDD and 28% less than DDD. Escitalopram and mirtazapine were the most commonly prescribed drugs. Both did not find mention in the National List of Essential Medicines and World Health Organization–Essential Medicines List (EML). Out of 214 prescriptions, 209 prescriptions were for psychiatric indications and the rest 5 were for nonpsychiatric indications. TCAs were prescribed more for psychiatric indications other than depression, while SSRIs were prescribed equally for depression and other psychiatric indications. Conclusion: Prescription trend in this study is in consonance with other contemporary studies. Extensive use of mirtazapine is a peculiar finding requiring further exploration. As in other studies, SSRIs have been used in doses more than their defined daily dose. Off-label use of antidepressants is widespread, but it should be backed by drug-specific robust evidence. EMLs and clinical usage derive from each other and need to be in mutual sync.